Virus Detection in Questing Ticks is not a Sensitive Indicator for Risk Assessment of Tick‐Borne Encephalitis in Humans. (6th July 2012) - Stefanoff, P.; Pfeffer, M.; Hellenbrand, W.; Rogalska, J.; Rühe, F.; Makówka, A.; Michalik, J.; Wodecka, B.; Rymaszewska, A.; Kiewra, D.; Baumann‐Popczyk, A.; Dobler, G.
Summary Tick‐borne encephalitis virus (TBEV) is the most important tick‐transmitted arbovirus causing human disease in Europe, but information on its endemic occurrence varies between countries because of differences in surveillance systems. Objective data are necessary to ascertain the disease risk for vaccination recommendations and other public health interventions. In two independent, separately planned projects, we used real‐time RT‐PCR to detect TBE virus in questing ticks. In Poland, 32 sampling sites were selected in 10 administrative districts located in regions where sporadic TBE cases were reported. In Germany, 18 sampling sites were selected in two districts located in a region with high TBE incidence. Altogether, >16 000 ticks were tested by real‐time RT‐PCR, with no sample testing positive for TBEV. A systematic search for published studies on TBEV prevalence in ticks in Poland and Germany also suggested that testing large numbers of collected ticks could not consistently assure virus detection in known endemic foci. Although assignment of results to administrative regions is essential for TBE risk mapping, this was possible in only 10 (investigating 22 417 ticks) of 15 published studies (>50 000 ticks) identified. We conclude that the collection and screening of ticks by real‐time RT‐PCR cannot be recommended for assessment of human TBE risk. Alternative methods of environmental TBEV monitoring should be considered, such as serological monitoring of rodents or other wildlife.